Method for recycling fiber-reinforced thermosetting composite material by catalytic oxidation method

By using nano-scale cerium oxide catalyst in polar solvents to decompose fiber-reinforced thermoset composites under mild conditions, the problems of catalyst toxicity, high cost and high degradation temperature in the prior art are solved, and high efficiency and low energy consumption fiber recovery is achieved and resin degradation, suitable for industrial applications.

CN119144046APending Publication Date: 2024-12-17CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310710907.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the prior art, when recycling waste fiber reinforced thermoset composite materials, the catalyst has toxicity and high cost, and the degradation temperature is high and energy consumption is high, making it difficult to achieve effective degradation at low temperature.

Method used

Nano-scale cerium oxide is used as a catalyst, and catalytic degradation is carried out by uniform dispersing in a polar solvent and performing catalytic degradation under mild conditions of 100-180°C. After the degradation is completed, the fibers and recovery liquid are filtered, and the catalyst can be recycled.

Benefits of technology

It achieves efficient degradation of thermoset composite materials at lower temperatures, with high degradation efficiency, low energy consumption, and no toxicity of catalysts. The process flow is simplified, and the degraded fiber performance is maintained well, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention aims to provide a method for recovering a fiber-reinforced thermosetting composite material by a catalytic oxidation method, which comprises the following steps: (1) cutting the composite material, and immersing the cut composite material in an organic solvent for pretreatment so as to swell the composite material; (2) uniformly dispersing nanoscale cerium oxide serving as a catalyst into a polar solvent to obtain a polar solvent with the catalyst; and (3) placing the pretreated composite material in a polar solvent with a catalyst, heating to 100-180 DEG C, carrying out catalytic degradation, and filtering after degradation is completed to obtain reinforced fibers and a recovery liquid. The degradation reaction can be carried out at a low temperature, and the reaction catalyst has no toxicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of thermosetting resin degradation and resource utilization, and specifically relates to a method for recycling fiber-reinforced thermosetting composite materials by a catalytic oxidation method. Background Art

[0002] Thermosetting resins are widely used in wind turbine blades, electronic appliances, aerospace, floor paint and other industries due to their excellent properties such as light weight, high strength, excellent electrical properties and good corrosion resistance. In particular, with the introduction of the new energy industry as a national strategic emerging industry plan, the wind power industry has developed rapidly, and thermosetting resins account for about a quarter of wind turbine blades. Wind turbine blades that have reached the end of their service are one of the main sources of waste thermosetting resins, and scraps and defective products generated during the production and processing process are another major source of waste thermosetting resins. However, thermosetting resin waste has an insoluble and infusible three-dimensional cross-linked network structure and cannot be processed secondary, which makes it difficult to recycle, and there are problems such as poor recycling efficiency and serious pollution.

[0003] At present, waste thermosetting resins are mainly disposed of by landfill or incineration. Rough treatment methods will lead to water, soil and air pollution, posing a serious threat to sustainable development. Some countries have banned incineration and set requirements for landfill ratios. In addition, most thermosetting resins are prepared using non-renewable resources such as petroleum and fossil raw materials. Therefore, exploring efficient recycling solutions is of great significance in reducing dependence on limited petroleum resources, avoiding waste accumulation in the environment, reducing greenhouse gas emissions, improving resource utilization, creating potential economic value, improving the environment and developing a circular economy, which is conducive to the realization of carbon neutrality goals.

[0004] The research on the recycling methods of waste fiber-reinforced thermosetting composites at home and abroad is mainly aimed at the treatment of non-degradable thermosetting resin-based composite waste. Thermosetting resins mainly include unsaturated polyester resins, epoxy resins, polyurethane resins, etc. The treatment methods include landfill, incineration, crushing, heat treatment and solvent degradation.

[0005] Waste fiber-reinforced thermosetting composites can be recycled and utilized through solvent degradation. Specifically, a degradation liquid is formed by combining a catalyst and an organic solvent, and a heating reaction is performed to promote the degradation of the thermosetting resin and separate it from the reinforcing fibers. Thus, the cracked resin and fibers can be extracted separately, and the degradation solvent can be recovered for reuse, thus completing the degradation and recycling process of waste fiber-reinforced thermosetting composites.

[0006] CN 115636980 A discloses a wind turbine blade recycling method based on catalytic degradation, wherein a catalytic degradation catalyst is prepared by using vanadium oxide as an active component and titanium dioxide as a carrier to degrade the resin matrix of the wind turbine blade. The disadvantages are: the metal oxide of vanadium is toxic and harmful to the environment; the degradation needs to be carried out at a temperature of 250°C to 280°C, the degradation temperature is relatively high, and the energy consumption is relatively large.

[0007] CN 114589196 A discloses a method for recovering thermosetting resin and composite materials by mild oxidative degradation, which uses a high-valent metal salt as a catalyst to degrade the thermosetting resin and composite materials under mild conditions. The high-valent metal salt catalyst used is relatively expensive and toxic (such as ammonium cerium nitrate), and the catalyst recovery process is relatively complicated. Summary of the invention

[0008] The object of the present invention is to provide a method for recycling fiber-reinforced thermosetting composite materials by catalytic oxidation, so that the degradation reaction can be carried out at a lower temperature and the reaction catalyst is non-toxic.

[0009] To achieve the above object, the present invention adopts the following technical solutions:

[0010] A method for recycling fiber-reinforced thermosetting composite materials by catalytic oxidation, comprising the following steps:

[0011] (1) cutting the composite material and immersing it in an organic solvent for pretreatment to allow it to swell;

[0012] (2) uniformly dispersing nano-sized cerium oxide as a catalyst in a polar solvent to obtain a polar solvent with a catalyst;

[0013] (3) Then, the pretreated composite material is placed in a polar solvent containing a catalyst and heated to 100-180° C. for catalytic degradation. After the degradation is completed, the composite material is filtered to obtain reinforcing fibers and a recovery liquid.

[0014] In step (1) of the present invention, the cut composite material is immersed in a suitable organic solvent for swelling. The specific solvent is well known in the art, such as methanol, ethanol, acetic acid and phenol. In a preferred embodiment, the organic solvent is acetic acid. During pretreatment, the cut composite material is immersed in a reflux device containing acetic acid and heated to 80-120°C to pretreat the composite material to facilitate subsequent catalyst degradation.

[0015] Preferably, in step (1), the volume of acetic acid used is at least twice the volume of the composite material, and the heating treatment time is not less than 0.5 h, preferably 1-2 h.

[0016] In step (1) of the present invention, those skilled in the art will appreciate that the composite material, for example, of fiber and thermosetting resin, can be crushed or cut into blocks or particles. The smaller the size after crushing, the more conducive it is to subsequent degradation. However, the crushing cost will increase as the size of the crushed material decreases. In actual application, the size of the crushed material can be determined according to actual application requirements. Usually, the crushed material can be in granular form. For example, after crushing or cutting, the particles can be no larger than 5 cm, such as 3 cm or 1 cm.

[0017] In step (2) of the present invention, the catalyst is uniformly dispersed in a polar solvent for subsequent use in a degradation reaction; the polar solvent may be one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylformamide, formic acid and acetic acid.

[0018] In the present invention, the catalyst is nano-scale cerium oxide, which is non-toxic and does not cause secondary pollution to the environment. In a preferred embodiment, in order to improve the catalytic effect, the preparation method of the nano-scale cerium oxide is as follows:

[0019] Cerium nitrate, sodium acetate and surfactant are mixed uniformly in a molar ratio of 1:(3-5):(1-4), such as 1:4:2 or 1:4:3, and then cooled after the reaction is completed in a reactor at 180-200°C; the reaction product is washed with anhydrous ethanol and centrifuged to remove the surfactant on the surface, and then dried and broken up to obtain a nano-scale cerium oxide product; preferably, the reactor is a microwave high-pressure reactor, and the reaction time is 6-8h.

[0020] Preferably, the surfactant is cetyltrimethylammonium bromide, Triton X-100 and / or sodium dodecyl sulfate, so as to facilitate emulsification during the preparation process and prevent product agglomeration.

[0021] In some embodiments, in step (2), the mass ratio of the catalyst to the polar solvent is 1:(5-20), such as 1:8, 1:10 or 1:15.

[0022] In step (3) of the present invention, the composite material is added to a polar solvent with a catalyst and heated to 100-180°C, such as 120°C, 140°C or 160°C for catalytic degradation. Of course, those skilled in the art will appreciate that higher temperatures can also achieve degradation, but it is not conducive to controlling energy consumption. Among them, the relative amount of the composite material added should not be too little or too much. Too little processing costs are high, and too much is not conducive to contact with the solvent and the catalyst. In some embodiments, the mass ratio of the composite material to the polar solvent is 1: (1-4), such as 1: 2 or 1: 3.

[0023] In some embodiments, the reaction time of the catalytic degradation in step (3) may be 4 to 10 hours, such as 6 hours or 8 hours. Of course, those skilled in the art will appreciate that the specific reaction time may also be affected by the properties of the composite material itself, the cutting size, the swelling effect, and the like.

[0024] In step (3) of the present invention, after the degradation is completed, the fibers in the composite material will be dispersed in the solvent, and the reinforcing fibers can be obtained by filtering, and the recovered liquid obtained after filtering contains nano-scale cerium oxide. It is understood by those skilled in the art that the cerium oxide catalyst can be separated from the much larger fibers by controlling the filter pore size during filtration, for example, the filter pore size can be 100-200 mesh (Tyler standard sieve), and the fibers can be washed with a solvent such as the recovered solvent after filtration.

[0025] In some embodiments, the method further comprises step (4): subjecting the recovered liquid to centrifugal treatment to recover the cerium oxide catalyst for recycling; and the solvent can be further recovered from the separated liquid phase.

[0026] In the present invention, the fiber-reinforced thermosetting composite material may be a wind turbine blade or other resin composite materials.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] The invention adopts nano cerium oxide as a catalyst for composite material resin degradation. The catalyst has many active centers on the catalyst surface and good selectivity. When used as a resin degradation catalyst, the catalytic efficiency can be significantly improved. The degradation reaction can be carried out at a relatively low temperature, such as below 200 DEG C or further below 180 DEG C, so that the CN or CO bond in the composite material is broken, the energy consumption is low, and the performance damage to the fiber is small. The solvent and the catalyst can be recycled and reused after the reaction, the separation is simple, the catalyst is non-toxic, and no secondary pollution is caused to the environment. The catalyst raw material source is abundant, the cost is low, the degradation reaction process is simple, the equipment requirement is low, and it is convenient for industrial production. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiment of the present invention. Obviously, the described embodiment is only an embodiment of a part of the present invention, rather than all embodiments. It should be understood that the implementation described below can adopt alternative variations and implementations. It should also be understood that the specific products, compositions and / or methods described herein are exemplary and should not be considered restrictive. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work should fall within the scope of protection of the present invention.

[0030] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0031] Unless otherwise expressly stated, the term "substantially" used herein, such as "substantially the same", will be understood to encompass parameters with fluctuations within a suitable range, such as ±10% or ±15% fluctuations of the parameter. In some embodiments, the range of fluctuations is within ±10%.

[0032] Unless otherwise specified, all reagents used in the following examples / comparative examples were of analytical grade.

[0033] The preparation method of the composite materials used in the following embodiments / comparative examples is as follows: the resin adopts the epoxy resin LT-5089A / B provided by Huibai New Materials Technology (Shanghai) Co., Ltd., and the glass fiber adopts the glass fiber cloth provided by Changzhou Tianma Group Co., Ltd., and is prepared by a vacuum bag pressing process. Before use, the average tensile strength of the original glass fiber monofilament was tested to be 2.27 GPa.

[0034] Test method:

[0035] Composite material degradation rate = (composite material mass before degradation - composite material mass after degradation) / (composite material mass before degradation - fiber mass) × 100%,

[0036] The quality of the composite material after degradation: the degradation liquid after the composite material is degraded is filtered, the solid product obtained after filtration is washed with alcohol, and the solid product is placed in a vacuum drying oven at 150°C and dried for 24 hours before being weighed;

[0037] Fiber quality: The degraded solid product was heated in a muffle furnace at 550°C for 2 hours to remove the residual undegraded resin, and then weighed.

[0038] The fiber strength test was conducted in the tensile mode of DMA Q800 at a tensile rate of 50 μm / min until it broke. The ratio of the measured value to the original fiber strength indicates the strength retention rate of the recycled fiber. The greater the retention rate, the less damage the degradation process has on the recycled fiber.

[0039] The specific preparation method of the nano cerium oxide catalyst 1 of the present invention is as follows:

[0040] 100 ml of 0.5 mol / L cerium nitrate aqueous solution, 16.4 g of sodium acetate, and 36.4 g of cetyltrimethylammonium bromide (CTAB) are mixed evenly, then placed in a microwave high-pressure reactor, reacted at 180° C. for 6 hours, then the heating is turned off, and the mixture is slowly cooled to room temperature along with the furnace temperature; the reaction product is washed with anhydrous ethanol, centrifuged to remove impurities, and then dried in a 60° C. vacuum oven to constant weight, and then broken up to obtain a nano-scale cerium oxide product.

[0041] The specific preparation method of the nano cerium oxide catalyst 2 of the present invention is as follows:

[0042] 100 ml of 1.0 mol / L cerium nitrate aqueous solution, 32.8 g of sodium acetate, and 115.2 g of sodium dodecyl sulfate were mixed evenly, and then placed in a microwave high-pressure reactor. After reacting at 200° C. for 8 hours, the heating was turned off, and the mixture was slowly cooled to room temperature along with the furnace temperature. The product after the reaction was washed with anhydrous ethanol, centrifuged to remove impurities, and dried in a vacuum oven at 60° C. to constant weight, and then broken up to obtain a nano-scale cerium oxide product.

[0043] The specific preparation method of the nano cerium oxide catalyst 3 of the present invention is as follows:

[0044] The difference from the preparation method of catalyst 1 is that the amount of sodium acetate used is 12.3 g, the surfactant is Triton X-100, and the amount used is 97.1 g; the rest is the same as the preparation method of catalyst 1.

[0045] The specific preparation method of the nano cerium oxide catalyst 4 of the present invention is as follows:

[0046] Referring to the description of Example 1 in CN114477264A, nano cerium oxide was prepared by the sol-gel method:

[0047] 110 ml of triethanolamine was gradually added to 100 ml of 2.0 mol / L cerium chloride aqueous solution. After the reaction generated cerium hydroxide precipitate, triethanolamine was continued to be added until the triethanolamine was added and the cerium hydroxide precipitate was completely dissolved. After the solution was clarified, it was heated to 55°C to generate a wet gel.

[0048] The obtained wet gel was washed and filtered 3 times with ethanol, and then washed and filtered 3 times with deionized water; after washing and filtering, the obtained wet gel was placed in an oven at 150° C. and dried for 24 hours to remove moisture to obtain a dry gel;

[0049] The obtained dry gel is placed in a muffle furnace and burned. The temperature is raised to 650°C within 4 hours for thermal decomposition. The dry gel is calcined at 650°C for 4 hours. The temperature is lowered to room temperature and the dry gel is dispersed to obtain nano cerium oxide.

[0050] The following examples 1-4 use catalyst 1 for degradation:

[0051] Example 1

[0052] The thermosetting composite material was cut into small pieces of about 30mm*30mm*5mm, weighing 8.52g, immersed in a reflux device containing acetic acid, the volume of acetic acid was 50ml, the reflux device was heated to 80°C, the heating time was 2h, and then the composite material was taken out and washed with deionized water and placed in a 120°C oven to dry to constant weight. 47.5g N-methylpyrrolidone and 2.5g nano-cerium oxide catalyst 1 were mixed evenly by high-speed stirring, and then added to the treated composite material, placed in a closed autoclave and heated to 120°C for 3h for catalytic degradation. After the degradation was completed, the reinforcing fiber was filtered and recovered. The fiber was washed with alcohol and dried and weighed to 6.28g. The recovered liquid was centrifuged to recover the nano-cerium oxide catalyst for recycling.

[0053] In this embodiment, the resin degradation rate is 92.6%, and the fiber strength retention rate is 95.7%.

[0054] Example 2

[0055] The thermosetting composite material was cut into small pieces of about 30mm*30mm*5mm, weighing 8.33g, immersed in a reflux device containing acetic acid, the volume of acetic acid was 50ml, the reflux device was heated to 100℃, the heating time was 1h, and then the composite material was taken out and washed with deionized water and placed in a 120℃ oven to dry to constant weight. 45.0g N-methylpyrrolidone and 5.0g nano-cerium oxide catalyst 1 were mixed evenly by high-speed stirring, and then added to the treated composite material, placed in a closed autoclave and heated to 140℃ for 4h for catalytic degradation. After the degradation was completed, the reinforcing fiber was filtered and recovered. The fiber was washed with alcohol and dried and weighed to 6.05g. The recovered liquid could be recovered by centrifugation. The nano-cerium oxide catalyst can be recycled.

[0056] In this embodiment, the resin degradation rate is 96.4%, and the fiber strength retention rate is 94.1%.

[0057] Example 3

[0058] The thermosetting composite material was cut into small pieces of about 30mm*30mm*5mm, weighing 8.89g, immersed in a reflux device containing acetic acid, the volume of acetic acid was 50ml, the reflux device was heated to 80℃, the heating time was 2h, and then the composite material was taken out and washed with deionized water and placed in a 120℃ oven to dry to constant weight. 42.5g acetic acid and 7.5g nano-cerium oxide catalyst 1 were mixed evenly by high-speed stirring, and then added to the treated composite material, placed in a closed autoclave and heated to 120℃ for 2.5h for catalytic degradation. After the degradation was completed, the reinforcing fiber was filtered and recovered. The fiber was washed with alcohol and dried and weighed to 6.41g. The recovered liquid could be recovered by centrifugation. The nano-cerium oxide catalyst can be recycled.

[0059] In this embodiment, the resin degradation rate is 98.2%, and the fiber strength retention rate is 97.2%.

[0060] Example 4

[0061] The thermosetting composite material was cut into small pieces of about 30mm*30mm*5mm, weighing 7.92g, immersed in a reflux device containing acetic acid, the volume of acetic acid was 50ml, and the reflux device was heated to 120℃ for 1h, then the composite material was taken out and washed with deionized water and placed in a 120℃ oven to dry to constant weight. 40g N,N dimethylformamide and 10g nano cerium oxide catalyst 1 were mixed evenly by high-speed stirring, and then added to the treated composite material, placed in a closed autoclave and heated to 160℃ for 4h for catalytic degradation. After the degradation was completed, the reinforcing fiber was filtered and recovered. The fiber was washed with alcohol and dried and weighed to 5.78. The recovered liquid was centrifuged to recover the nano cerium oxide catalyst for recycling.

[0062] In this embodiment, the resin degradation rate is 95.1%, and the fiber strength retention rate is 93.5%.

[0063] The following examples 5-8 use catalyst 2 for degradation:

[0064] Example 5

[0065] The thermosetting composite material is cut into small pieces of about 30mm*30mm*5mm, weighing 8.72g, immersed in a reflux device containing acetic acid, the volume of acetic acid is 100ml, the reflux device is heated to 80℃, the heating time is 1h, and then the composite material is taken out and washed with deionized water and placed in a 120℃ oven to dry to constant weight. 47.5g of dimethyl sulfoxide and 2.5g of nano-cerium oxide catalyst 2 are mixed evenly by high-speed stirring, and then the treated composite material is added, placed in a closed autoclave and heated to 120℃ for 3h for catalytic degradation. After the degradation is completed, the reinforcing fiber is filtered and recovered. The fiber is washed with alcohol and dried and weighs 6.51g. The recovered liquid can be recycled by centrifugation to recover the nano-cerium oxide catalyst.

[0066] In this embodiment, the resin degradation rate is 89.2%, and the fiber strength retention rate is 96.4%.

[0067] Example 6

[0068] The thermosetting composite material is cut into small pieces of about 30mm*30mm*5mm, weighing a mass of 9.11g, immersed in a reflux device containing acetic acid, the volume of acetic acid is 100ml, the reflux device is heated to 120℃, the heating time is 1h, and then the composite material is taken out and washed with deionized water and placed in a 120℃ oven to dry to constant weight. 45.0g N-methylpyrrolidone and 5.0g nano-cerium oxide catalyst 2 are mixed evenly by high-speed stirring, and then added to the treated composite material, placed in a closed autoclave and heated to 140℃, and the heating time is 4h for catalytic degradation. After the degradation is completed, the reinforcing fiber is filtered and recovered. The fiber is washed with alcohol and dried and weighs 6.68g. The recovered liquid can be recycled by centrifugation to recover the nano-cerium oxide catalyst.

[0069] In this embodiment, the resin degradation rate is 93.9%, and the fiber strength retention rate is 93.3%.

[0070] Example 7

[0071] The thermosetting composite material is cut into small pieces of about 30mm*30mm*5mm, weighing 7.89g, immersed in a reflux device containing acetic acid, the volume of acetic acid is 50ml, the reflux device is heated to 80℃, the heating time is 2h, and then the composite material is taken out and washed with deionized water and placed in a 120℃ oven to dry to constant weight. 42.5g formic acid and 7.5g nano-cerium oxide catalyst 2 are mixed evenly by high-speed stirring, and then added to the treated composite material, placed in a closed autoclave and heated to 120℃, the heating time is 2h for catalytic degradation, and after the degradation is completed, the reinforcing fiber is filtered and recovered. The fiber is washed with alcohol and dried and weighs 5.71g. The recovered liquid can be recycled by centrifugation to recover the nano-cerium oxide catalyst.

[0072] In this embodiment, the resin degradation rate is 97.3%, and the fiber strength retention rate is 96.2%.

[0073] Example 8

[0074] The thermosetting composite material was cut into small pieces of about 30mm*30mm*5mm, weighing 8.92g, immersed in a reflux device containing acetic acid, the volume of acetic acid was 80ml, the reflux device was heated to 120℃, the heating time was 1h, and then the composite material was taken out and washed with deionized water and placed in a 120℃ oven to dry to constant weight. 40g N,N-dimethylacetamide and 10g nano-cerium oxide catalyst 2 were mixed evenly by high-speed stirring, and then added to the treated composite material, placed in a closed autoclave and heated to 160℃ for 4h for catalytic degradation. After the degradation was completed, the reinforcing fiber was filtered and recovered. The fiber was washed with alcohol and dried and weighed to 6.55g. The recovered liquid could be recovered by centrifugation. The nano-cerium oxide catalyst can be recycled.

[0075] In this embodiment, the resin degradation rate is 93.6%, and the fiber strength retention rate is 92.7%.

[0076] Example 9 (using catalyst 3)

[0077] The difference from Example 3 is that the catalyst 1 is replaced by catalyst 3, the degradation temperature is 100° C., and the rest is the same.

[0078] In this embodiment, the resin degradation rate is 90.6%, and the fiber strength retention rate is 96.8%.

[0079] Example 10 (using catalyst 4)

[0080] The difference from Example 7 is that the catalyst 2 is replaced by catalyst 4, and the rest is the same.

[0081] In this embodiment, the resin degradation rate is 80.7%, and the fiber strength retention rate is 90.8%.

[0082] It can be seen from the above embodiments that the scheme of the present invention can complete the degradation of fiber-reinforced composite material resin in a relatively short period of time, and at the same time the recycled fibers can better maintain their strength, which is convenient for reuse.

[0083] Comparative Example 1

[0084] The thermosetting composite material was cut into small pieces of about 30mm*30mm*5mm, weighed to 8.42g, immersed in a reflux device containing acetic acid, the volume of acetic acid was 50ml, the reflux device was heated to 80°C, the heating time was 1h, and then the composite material was taken out and washed with deionized water and placed in a 120°C oven to dry to constant weight. The treated composite material was added to 50g of N-methylpyrrolidone, placed in a closed autoclave and heated to 120°C for 3h for catalytic degradation. After the degradation was completed, the reinforcing fibers were filtered and recovered.

[0085] The resin degradation rate in this embodiment is 5.9%, and basically no degradation is achieved.

[0086] Comparison between Comparative Example 1 and Example 1 shows that without adding cerium oxide nanocatalyst into the degradation solution, the fiber reinforced composite material can basically not be degraded under the same conditions.

[0087] Comparative Example 2

[0088] The difference from Example 7 is that the catalyst 2 is replaced by the V2O5 / TiO2 catalyst used in CN115636980A, and the rest is the same.

[0089] The V2O5 / TiO2 catalyst is prepared by the following method (see paragraph 0039 of CN115636980A): 14.2g of ammonium metavanadate is weighed and added to 100ml of water, and the pH of the system is adjusted to 9 with ammonia water and then stirred, and then stirred to completely dissolve the ammonium metavanadate; then 100g of nano-titanium dioxide is added to the mixed solution, and after continuing to stir evenly, the mixed solution is dried at 100°C for 4h; finally, it is calcined at 500°C for 3.5h to obtain a V2O5 / TiO2 catalyst; in the obtained V2O5 / TiO2 catalyst, the mass percentage of V2O5 is 10%.

[0090] The resin degradation rate in this comparative example is 15.5%, which is too low to obtain a single fiber for strength retention test.

[0091] Comparison between Comparative Example 2 and Example 7 shows that the V2O5 / TiO2 catalyst system cannot complete the degradation of the fiber-reinforced composite material under the temperature conditions of this solution.

Claims

1. A method for recycling fiber-reinforced thermosetting composite materials by catalytic oxidation, characterized in that: The following steps are involved: (1) cutting the composite material and immersing it in an organic solvent for pretreatment to allow it to swell; (2) uniformly dispersing nano-sized cerium oxide as a catalyst in a polar solvent to obtain a polar solvent with a catalyst; (3) Then, the pretreated composite material is placed in a polar solvent containing a catalyst and heated to 100-180° C. for catalytic degradation. After the degradation is completed, the composite material is filtered to obtain reinforcing fibers and a recovery liquid.

2. The method according to claim 1, characterized in that In step (1), the organic solvent is acetic acid; during pretreatment, the composite material is cut and immersed in a reflux device containing acetic acid and heated to 80-120° C. to pretreat the composite material.

3. The method according to claim 2, characterized in that In step (1), the volume of acetic acid is at least twice the volume of the composite material, and the heating treatment time is not less than 0.5 h, preferably 1-2 h.

4. The method according to any one of claims 1 to 3, characterized in that In step (2), the preparation method of nano-scale cerium oxide as a catalyst is as follows: Cerium nitrate, sodium acetate and surfactant are mixed uniformly in a molar ratio of 1:(3-5):(1-4), and then cooled after the reaction is completed in a reactor at 180-200° C.; the reaction product is washed with anhydrous ethanol, centrifuged to remove impurities, and then dried and broken up to obtain a nano-scale cerium oxide product; preferably, the reactor is a microwave high-pressure reactor, and the reaction time is 4-10 hours.

5. The method according to claim 4, characterized in that The surfactant is cetyltrimethylammonium bromide, Triton X-100 and / or sodium dodecyl sulfate.

6. The method according to any one of claims 1 to 5, characterized in that In step (2), the mass ratio of the catalyst to the polar solvent is 1:(5-20).

7. The method according to any one of claims 1 to 6, characterized in that The polar solvent is one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylformamide, formic acid and acetic acid.

8. The method according to any one of claims 1 to 7, characterized in that In step (3), the reaction time of the catalytic degradation is 6 to 8 hours; and the mass ratio of the composite material to the polar solvent is 1:(1 to 4).

9. The method according to any one of claims 1 to 8, characterized in that The method further comprises step (4): centrifuging the recovered liquid to recover the cerium oxide catalyst for recycling.

10. The method according to any one of claims 1 to 9, characterized in that The composite material is a wind turbine blade; preferably, during pretreatment, the composite material is cut into particles with a size not exceeding 5 cm.

Citation Information

Patent Citations

  • Method for preparing nano cerium oxide by sol-gel method

    CN114477264A

  • Method for recycling thermosetting resin and composite material thereof through mild oxidative degradation

    CN114589196A

  • Wind power blade recovery method based on catalytic degradation

    CN115636980A